(untitled) (Journal of Academic Finance, 2020)
This article examines the plausible effect of the Covid-19 pandemic on shareholder behavior in the sub-regional stock market. Behavior that we captured with three indicators: demand, supply and exchange of shares. To assess the effect of the pandemic on the evolution of these parameters, we created a thirteen months database, split into seven months before the pandemic and six since the onset of the pandemic. At the end of a series of paired samples "t" tests, it appears that neither the supply, nor the demand, nor the exchange of shares have undergone a significant change over the period before and during the pandemic. Several explanatory factors justify this finding. We cite among others, the feverishness of the sub-regional stock market, in particularly the “shares” compartment; the loss of jobs caused by the pandemic; the communicating vessels existing between the flow of securities of each of the companies listed on the market and the virtual non-existence of exchanges of securities. For further studies, a similar study will be carried out on the “bonds” compartment of the market.